2014
DOI: 10.1371/journal.pone.0087946
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Out of Hours Presentation with Acute Stroke on Processes of Care and Outcomes: Analysis of Data from the Stroke Improvement National Audit Programme (SINAP)

Abstract: BackgroundThere is inconsistent evidence that patients with stroke admitted to hospital out of regular working hours (such as weekends) experience worse outcomes. We aimed to identify if inequalities in the quality of care and mortality exist in contemporary stroke care in England.MethodsSINAP is a prospective database of acute stroke patients, documenting details of processes of care over the first 72 hours. We compared quality of care indicators and mortality at 72 hours, 7 days and 30 days, for patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 19 publications
3
45
0
Order By: Relevance
“…The study by Turner et al 4 adds to this body of literature, describing quality of care and outcomes in a large cohort of patients with stroke in Scotland. As previous studies have observed,5 they found that patients admitted on weekends and overnight were generally sicker than those admitted during weekends, with a higher prevalence of haemorrhagic stroke and markers of poor prognosis. Quality was poorer overnight and on weekends for some processes of care (swallow screening, thrombolysis) but not for others (brain scanning, administration of aspirin).…”
supporting
confidence: 62%
“…The study by Turner et al 4 adds to this body of literature, describing quality of care and outcomes in a large cohort of patients with stroke in Scotland. As previous studies have observed,5 they found that patients admitted on weekends and overnight were generally sicker than those admitted during weekends, with a higher prevalence of haemorrhagic stroke and markers of poor prognosis. Quality was poorer overnight and on weekends for some processes of care (swallow screening, thrombolysis) but not for others (brain scanning, administration of aspirin).…”
supporting
confidence: 62%
“…However, analysis of 10,987 ICH patients from the Canadian Hospital Discharge Database showed no significant difference of in-hospital mortality between weekend and weekday admission [16] . Discrepancies across studies may be attributable to differences in the availability of organized specialist stroke care, defined by the use of stroke units [20,21] , quality of care checklists [5] , and patient-staff ratio [3] during off-hours. In the present analysis of INTERACT2, where all participants received a standardized treatment protocol and background management according to best practice acute stroke care [17,18] , there was no difference in outcome between off-and on-hour admission.…”
Section: Discussionmentioning
confidence: 99%
“…Different staffing models are seen for “regular” working hours compared to “off-hours.” The so-called weekend effect, in addition to admission during off hours such as nights and holidays, can negatively impact mortality and outcome for stroke patients [16,17,18,19,20,21]. Several studies have been published which look at the effect staffing has on the mortality and functional outcome of stroke patients.…”
Section: Nursing Stroke Care: From the Emergency Department Over The mentioning
confidence: 99%
“…Several studies have been published which look at the effect staffing has on the mortality and functional outcome of stroke patients. During off-hours, patients are noted to wait longer for diagnostic imaging and admission [17,18]. An increase in the number of patients eligible for IV alteplase is often seen on the weekend - however, there are decreased odds of receiving the medication on the weekend [16,17,18].…”
Section: Nursing Stroke Care: From the Emergency Department Over The mentioning
confidence: 99%
See 1 more Smart Citation